The applied theatre reader - Prentki, Tim; Preston, Sheila (Routledge, 2021)
The Applied Theatre Reader is the first book to bring together new case studies of practice by leading practitioners and academics in the field and beyond, with classic source texts from writers such as Noam Chomsky, bell hooks, Mikhail Bakhtin, Augusto Boal and Chantal Mouffe. This new edition brings the field fully up to date with the breadth of applied theatre practice in the twenty-first century, adding essays on playback theatre, digital technology, work with indigenous practitioners, inter-generational practice, school projects and contributors from South America, Australia and New Zealand. The Reader divides the field into key themes, inviting critical interrogation of issues in applied theatre whilst also acknowledging the multi-disciplinary nature of its subject, crossing fields like theatre in educational settings, prison theatre, community performance, theatre in conflict resolution, interventionist theatre and theatre for development. A new lexicon of Applied Theatre and further reading for every part will equip readers with the ideal tools for studying this broad and varied field. This collection of critical thought and practice is essential to those studying or participating in the performing arts as a means for positive change.